Freezing-in the pure dark axion portal - Arias, Paola; Sáez, Bastián Díaz; Jaeckel, Joerg (Journal of cosmology and astroparticle physics, 2025)
A Z 2 symmetry under which “dark” and “visible” fields transform differently can further seclude already dark particles. In a dark sector consisting of an axion-like particle and a dark photon the dominant interaction can then be via a dark photon-axion portal to the ordinary photon. If the axion is lighter than the dark photon it naturally emerges as a viable dark matter candidate. We explore its freeze-in production both in a standard high-reheating temperature and weak coupling as well as a low-reheating temperature and strong coupling regime. Cosmological constraints are taken into account to identify viable regions in parameter space. For the strong freeze-in regime, we highlight the possibility of probing it at B-factories, beam dump and collider experiments. We also briefly discuss a potential misalignment contribution to the dark matter density and delineate under which conditions it can be neglected.